Enhancing Safety Level at Construction Site Using Internet of Things (IoT) - Sajri, Nur Adibah; Omar, Roshartini; Sarpin, Norliana; Nordin, Zailawati (Research in Management of Technology and Business, 2024)
The construction sector’s poor safety record necessitates rapid safety instructions and efficient safety management efforts. Research in underground construction reveals that 80 to 90 percent of accidents stem from workers’ behavior, working conditions, or inadequate equipment. This study investigates variables influencing IoT use to enhance construction site safety, explores implementation challenges, and examines effective methods for leveraging IoT. Semi-structured interviews were conducted with assistant engineers and site safety supervisors from Grade 7 companies employing IoT for safety enhancement. Sensors, RFID tagging, GPS, and drones commonly utilize IoT tools. Real-time monitoring, wearable integration, predictive maintenance, safety automation, data-driven decision-making, and enhanced worker communication emerged as key outcomes. IoT deployment is anticipated to reduce fatalities, injuries, and accidents in construction, improving compliance and productivity. Government benefits include worker protection, regulatory compliance, and financial gains. Academic institutions are crucial for promoting IoT technology advancement and safety processes through education, training, and research.